Search for anomalous couplings in boosted $ WW/WZ →\ellν\mathrm{ q \bar{q} }$ production in proton-proton collisions at $\sqrt{s} =$ 8 TeV - CMS collaboration (2235 authors) (2017)
This Letter presents a search for new physics manifested as anomalous triple gauge boson couplings in WW and WZ diboson production in proton–proton collisions. The search is performed using events containing a W boson that decays leptonically and a W or Z boson whose decay products are merged into a single reconstructed jet. The data, collected at s=8 TeV with the CMS detector at the LHC, correspond to an integrated luminosity of 19 fb−1 . No evidence for anomalous triple gauge couplings is found and the following 95% confidence level limits are set on their values: λ ( [−0.011,0.011] ), Δκγ ( [−0.044,0.063] ), and Δg1Z ( [−0.0087,0.024] ). These limits are also translated into their effective field theory equivalents: cWWW/Λ2 ( [−2.7,2.7] TeV−2 ), cB/Λ2 ( [−14,17] TeV−2 ), and cW/Λ2 ( [−2.0,5.7] TeV−2 ).